Building Socio-Ecological Resilience of Riparian Communities Through A Circular Economy: A Case Study of The Tersuara Program by PT Pertamina Patra Niaga Fuel Terminal Sei Siak - Sonny Ferdian; Hanifah Aufia Rahma; Dwi Tya Ramadhana (CV. Syntax Corporation Indonesia, 2026)
This research analyzed the implementation of the TERSUARA Program (Ternak Sumber Sari Sejahtera) as a circular economy-based social innovation initiated by PT Pertamina Patra Niaga Fuel Terminal Sei Siak in Tanjung Rhu Village, Pekanbaru. The program integrated riparian ecosystem conservation with a community-based integrated livestock system to generate simultaneous economic, social, and environmental value for vulnerable communities experiencing socio-ecological challenges. This research employed a qualitative descriptive case study design based on secondary data from academic literature and company internal documents, including social mapping reports, program implementation records, and community group financial statements. Data credibility was ensured through triangulation between theoretical frameworks and internal company evaluation findings. The TERSUARA Program successfully integrated vetiver grass-based ecological mitigation with an integrated circular livestock farming system consisting of goat farming, KUB native chicken farming, Black Soldier Fly (BSF) larvae cultivation, and the production of compost and liquid organic fertilizer. The program outcomes indicated that average participant income increased by 35%, group collective income increased by 25% between semesters, greenhouse gas (GHG) emissions were reduced by 1.648 tCO?-eq per year, and 100% of office organic waste (3,546 kg/year) was diverted from landfills and utilized as BSF larvae substrate. The findings were limited to the first year of implementation; therefore, future longitudinal studies over a 3–5-year period are recommended to evaluate long-term sustainability and impacts. This study provides empirical evidence of a circular corporate social responsibility (CSR) model that integrates ecological restoration with the economic empowerment of marginalized communities, demonstrating its potential for replication in other riparian areas across Indonesia as an integrated approach to achieving environmental sustainability and inclusive community development.